Plastic-Film Mulching for Enhanced Water-Use Efficiency and Economic Returns from Maize Fields in Semiarid China - Zhang, Peng; Wei, Ting; Cai, Tie; Ali, Shahzad; Han, Qingfang; Ren, Xiaolong; Jia, Zhikuan (Frontiers in Plant Science, 2017)
Maize (Zea mays L.) is the second most important cereal crop in China and it is sensitive to soil moisture stress, which can be alleviated when the soil surface is covered with plastic film to conserve humidity. During 2013 and 2014, maize was grown on a loess soil to evaluate several methods of plastic film mulch on soil water, soil temperature, water use efficiency (WUE), yield and revenue. The treatments included: (i) the control, conventional flat planting without plastic film mulch (CK); (ii) flat planting with maize rows (60 cm spacing) on plastic film mulch (70 cm wide); (iii) furrow planting of maize (60 cm spacing), separated by consecutive plastic film-mulched ridges (each 50 cm wide and 15 cm tall); (iv) furrow planting of maize (60 cm spacing), separated by alternating large and small plastic film-mulched ridges (large ridges: 70 cm wide and 15 cm tall, small ridges 50 cm wide and 10 cm tall); and (v) furrow-flat planting of maize (60 cm spacing) with a large plastic film-mulched ridge (60 cm wide and 15 cm tall) alternating with a flat without plastic film-mulched space (60 cm wide). Topsoil temperature (5–25 cm) was significantly (P<0.05) higher in field plots with plastic film mulch than the control (CK), and resulted in greater soil water storage (0-200 cm) up to 40 days after planting. Maize grain yield and water use efficiency (WUE) were significantly (P<0.05) higher with the furrow planting methods (consecutive film-mulched ridges and alternating film-mulched ridges) than the check in both years. Maize yield was, on average, 29% greater and 28% greater with these furrow planting methods, while the average WUE increased by 22.8% with consecutive film-mulched ridges and 21.1% with alternating film-mulched ridges. The two-year average net income increased by1559, 528, and 350 Chinese Yuan (CNY) ha-1 with the consecutive film-mulched ridges, furrow-flat planting and alternating film-mulched ridges, respectively, compared with the control (CK). We conclude that the consecutive film-mulched ridge method was the most productive and profitable for maize in this semi-arid area with limited and erratic precipitation.